Cutaneous manifestations of the Coronavirus Disease 2019 (COVID‐19): A brief review. Issue 4 (22nd May 2020) - Tang, Keyun; Wang, Yuanzhuo; Zhang, Hanlin; Zheng, Qingyue; Fang, Rouyu; Sun, Qiuning
Abstract: COVID‐19, first appeared in December 2019 in Wuhan, China, has been spreading quickly throughout the world. We reviewed the evidence on cutaneous manifestations of COVID‐19 based on PubMed database. The searching strategy was (COVID* or coronavirus*) and (dermatol* or skin* or cutaneous*). The publication time was limited to 2019 onward. After independent review by two authors, 14 studies with 228 confirmed cases were included in the analysis. A total of 60 patients developed skin rashes, and the age ranged from 8 to 84. Exanthematous eruptions potentially related to COVID‐19 infection were highly variable and heterogeneous. Skin lesions mainly appeared erythematous, urticarial, and vesicular (chicken pox‐like or varicelliform). Petechiae rash, livedo reticularis, and reactivation of oral HSV‐1 were also observed in single cases. Newly reported eruptions like vascular lesions and peculiar (perniosis‐like) skin lesions caused concern among dermatologists. Exanthems were widely distributed and were primarily located on the trunk. Associated symptoms, latency time, treatment, and prognosis were also carefully summarized. This study reviewed the recently published COVID‐19 studies with skin manifestations, which may pave the way for further research.